Ethanol vapor and saprophytic yeast treatments reduce decay and maintain quality of intact and fresh-cut sweet cherries - Jinhe Bai (2018)
The objective of this study was to evaluate the use of an ethanol vapor release pad and a saprophytic yeast Cryptococcus infirmo-miniatum (CIM) to reduce decay and maintain postharvest quality of intact or fresh-cut sweet cherries (Prunus avium) cv. Lapins and Bing. Intact or fresh-cut fruit were packed in perforated clamshells (capacity 454g) and stored at 1, 10 or 20°C for up to 21, 14 and 8d, respectively. For ethanol treatment, a pad made with silica gel powder containing 10g ethanol and covered with perforated film, which allows ethanol vapor to diffuse gradually, was attached to the upper lid of the clamshells. Ethanol treatment caused accumulation of ethanol in the packaging headspace, about 10μLL-1with little change within 14d at 1°C, 23μLL-1at d 1 and decreased to 15μLL-1at d 10 at 10°C, and 26μLL-1at d 1 and decreased to 13μLL-1at d 3 at 20°C. Ethanol content in fruit was less than 9mgkg-1in all the control fruit, and increased to 16, 34 and 43mgkg-1in ethanol-treated fruit at 1, 10 and 20°C, respectively. Nonetheless, a sensory taste panel did not perceive any flavor difference from the ethanol treatment. The ethanol treatment retarded softening, darkening, and acid decrease in fruit as well as discoloration of the stems, and extended shelf-life of intact cherries. Ethanol reduced brown rot (Monilinia fructicola) in fresh-cut cherries stored at 20°C, but not at 1 and 10°C. A pre-packaging dip in CIM completely controlled brown rot in inoculated fresh-cut cherries stored at 1°C, and in naturally infected cherries at 20°C. © 2011.